Access to Justice through Legal Aid: A Study in Bangladesh - Islam, Rabiul (American International Journal of Social Science Research, 2017)
Equal access to justice for the rich and poor alike is prerequisite to the maintenance of the rule of law. But the justice system through judicial administration is very costly in Bangladesh and that cost has been the most difficult factor for the poor and vulnerable sectors of people in case of getting justice. Thus an adequate legal aid system is one of the effective ways to ensure access to justice as well as to establish rule of law. In this paper attempts have been made to examine the present condition of the legal aid services in Bangladesh, the establishment and functions of the different legal aid committees but, importance is especially given to the local govt. level where legal aid services are provided by the District, Upazila and Union Legal Aid Committees. The study compares the role of the govt. and non- govt. organizations in dissemination of legal aid services among the people who do not manage themselves to get proper remedy due to various limitations and discriminations. After reviewing the collected data and analysis of these, it has observed that the cases to which legal aid services are provided include both the civil and criminal matters and the cases relating to family affairs. Finally conclusion is drawn after evaluating the activities of the aforesaid organizations and by making substantial recommendations to the concerned authority.